"To Establish Habits of Health": Health Education and Advice for Girls - Past, Present and Future - Varpalotai, Aniko; Singleton, Ellen (Atlantis, 2008)
This article examines school health textbooks covering almost one hundred and fifty years. The social construction of curriculum in public schools, particularly from the perspective of gender is examined through changes in conventional medical attitudes and beliefs and how sex education and sexuality were regulated for women through notions of moral "purity."